Overcoming Inferiority Feelings in Michael Gracey’s Movie the Greatest Showman (2017): An Individual Psychological Perspective - Chelsea Permata Jelita; M. Thoyibi (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2026)
This study analyzes the theme of overcoming feelings of inferiority in the film The Greatest Showman (2017), directed by Michael Gracey, through the lens of Alfred Adler's Individual Psychology. The research aims to identify indicators of the characters' feelings of inferiority, describe how these feelings are portrayed in the film, and explain why Michael Gracey addresses them in the narrative. Using literary studies, the study examines key scenes, character interactions, and musical performances to explore the psychological dimensions of marginalization and self-acceptance. The findings indicate that feelings of inferiority are portrayed through shame, low self-esteem, fear of social rejection, and sensitivity to public judgment, particularly among circus performers. This study concludes that feelings of inferiority play a central role in the film